Status of Biomass Derived Carbon Materials for Supercapacitor Application - Talam Kibona Enock; Cecil K. King’ondu; Alexander Pogrebnoi; Yusufu Abeid Chande Jande (International Journal of Electrochemistry)
Environmental concerns and energy security uncertainties associated with fossil fuels have driven the world to shift to renewable energy sources. However, most renewable energy sources with exception of hydropower are intermittent in nature and thus need storage systems. Amongst various storage systems, supercapacitors are the promising candidates for energy storage not only in renewable energies but also in hybrid vehicles and portable devices due to their high power density. Supercapacitor electrodes are almost invariably made of carbon derived from biomass. Several reviews had been focused on general carbon materials for supercapacitor electrode. This review is focused on understanding the extent to which different types of biomasses have been used as porous carbon materials for supercapacitor electrodes. It also details hydrothermal microwave assisted, ionothermal, and molten salts carbonization as techniques of synthesizing activated carbon from biomasses as well as their characteristics and their impacts on electrochemical performance.